2000
DOI: 10.1046/j.1365-2168.2000.01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in long-term survivors after curative transhiatal oesophagectomy for oesophageal carcinoma

Abstract: Patients who survive 2 years or more after transhiatal oesophageal resection for cancer can lead satisfactory lives. Although some residual symptoms may persist, their general quality of life is similar to that of healthy individuals of the same age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 17 publications
9
62
1
3
Order By: Relevance
“…In agreement with other studies, the largest improvement in quality of life was seen during the first months after surgery (Zieren et al, 1996;De Boer et al, 2000Brooks et al, 2002). It has previously been reported that some symptoms, such as early satiety, fatigue and diarrhoea, still persist in patients 2 years after oesophageal resection and without evidence of tumour recurrence (De Boer et al, 2000;Fagevik Olsen et al, 2005). Indeed, we found that nausea/vomiting, diarrhoea and fatigue were still present 13 months after surgery.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In agreement with other studies, the largest improvement in quality of life was seen during the first months after surgery (Zieren et al, 1996;De Boer et al, 2000Brooks et al, 2002). It has previously been reported that some symptoms, such as early satiety, fatigue and diarrhoea, still persist in patients 2 years after oesophageal resection and without evidence of tumour recurrence (De Boer et al, 2000;Fagevik Olsen et al, 2005). Indeed, we found that nausea/vomiting, diarrhoea and fatigue were still present 13 months after surgery.…”
Section: Discussionsupporting
confidence: 77%
“…Surgery for oesophageal cancer is often accompanied by significant morbidity (Zieren et al, 1996;Baba et al, 1997;McLarty et al, 1997;Blazeby et al, 2000;De Boer et al, 2000Brooks et al, 2002;Fagevik Olsen et al, 2005;Viklund et al, 2006). It has been reported that approximately 30% of patients will develop recurrent cancer within the first year after oesophageal resection.…”
mentioning
confidence: 99%
“…192 Some studies of survivors of head and neck cancers show that symptoms such as dysphagia, heartburn, altered taste and smell, and problems with saliva may persist, and are associated with greater functional impairment. 281,344 Physical sequelae of cancer such as stoma, scars and disfigurement, or Electrolarynx implantation may lead to social isolation and disruption of work, social life and intimacy. 345,346 Lymphoedema is also associated with substantial functional impairment and psychological morbidity.…”
Section: Physical Issues For Cancer Survivorsmentioning
confidence: 99%
“…Moreover, Rosmolen et al, in a longitudinal study, analyzed the quality of life among survivors of long periods 8 (minimum two years) after resection and reconstruction with transmediastinal gastric tube in 100 patients, also in patients with Adenoca. De Boer et al, in another longitudinal study, included 67% of Adenoca in the total sample studied and 28% of SCC 9 . In the first six months after surgery, during a variable period of time the patient experiences undesirable , and a quality of life that can be greatly impaired, returning to preoperative levels 7,11 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…There are comparative analysis of the quality of life of patients submitted to esophagectomy according to some surgical aspects, such as comparing the limited transhiatal resection to extensive transthoracic resection 5 ; between reconstruction with gastric tube and interposing the colon 6 ; comparison between curative esophagectomy and palliation 7,8 ; or even the comparison between the domains of quality of life with symptoms (physical and emotional) and factors related to illness and operation 9 . We did not found in the literature the possible differences between the quality of life of patients submitted to esophagectomy for Adenoca of the esophagogastric junction and the one of those submitted to esophagectomy by SCC.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%